Structures and properties of chicken myofibrillar protein gel induced by microwave heating. (27th January 2020) - Wei, Sumeng; Yang, Yuling; Feng, Xiao; Li, Shanshan; Zhou, Lei; Wang, Jingyu; Tang, Xiaozhi
Summary: Structures and properties of myofibrillar protein gel prepared at different power (300–800 W) were evaluated. Amino acid analysis demonstrated that changes in microwave power did not alter primary structure of gel. However, an increase in microwave power could change higher structures of gel. As microwave power increased, α‐helix content decreased and β‐sheet content increased. Increased microwave power probably facilitated protein to unfold and expose the internal groups, causing surface hydrophobicity and the formation of disulphide bonds were enhanced, which indicated changes in tertiary and quaternary structures of protein. At 500 W, gel had the best ultrastructure where surface morphology, springiness and water holding capacity reached the optimum. Our findings suggested that microwave at an appropriate power (500 W) could change higher structures of myofibrillar protein gel to achieve desired processing and quality protein gel characteristics. Abstract : Our research showed that microwave heating could improve the water holding capacity, appearance and textural properties of myofibrillar protein gels by changing their higher structures and microstructure.